Identifying SARS‐CoV‐2 'memory' NK cells from COVID‐19 convalescent donors for adoptive cell therapy. Issue 2 (2nd December 2021) - Herrera, Lara; Martin‐Inaraja, Myriam; Santos, Silvia; Inglés‐Ferrándiz, Marta; Azkarate, Aida; Perez‐Vaquero, Miguel A.; Vesga, Miguel A.; Vicario, Jose L.; Soria, Bernat; Solano, Carlos; De Paz, Raquel; Marcos, Antonio; et al.
Abstract: COVID‐19 disease is the manifestation of syndrome coronavirus 2 (SARS‐CoV‐2) infection, which is causing a worldwide pandemic. This disease can lead to multiple and different symptoms, being lymphopenia associated with severity one of the most persistent. Natural killer cells (NK cells) are part of the innate immune system, being fighting against virus‐infected cells one of their key roles. In this study, we determined the phenotype of NK cells after COVID‐19 and the main characteristic of SARS‐CoV‐2‐specific‐like NK population in the blood of convalescent donors. CD57+ NKG2C+ phenotype in SARS‐CoV‐2 convalescent donors indicates the presence of 'memory'/activated NK cells as it has been shown for cytomegalovirus infections. Although the existence of this population is donor dependent, its expression may be crucial for the specific response against SARS‐CoV‐2, so that, it gives us a tool for selecting the best donors to produce off‐the‐shelf living drug for cell therapy to treat COVID‐19 patients under the RELEASE clinical trial (NCT04578210). Abstract : SARS‐CoV‐2 infection induce a pro‐inflammatory environment that could lead to NK cells secreting IFN‐γ, increasing HLA‐E expression and being activated through NKG2C‐HLA‐E recognition. The NK cells become adaptive or "memory" cells that can recognize SARS‐CoV‐2 soluble peptides via NKG2C, triggering a specific inflammatory response to fight this virus.